Liquid-Phase Exfoliation of Arsenic Trisulfide (As2S3) Nanosheets and Their Use as Anodes in Potassium-Ion Batteries - Coleman, Jonathan; Jones, Lewys; Konkena, Bharathi; Nicolosi, Valeria (My University, 2024)
Here, we demonstrate the production of 2D nanosheets of arsenic disulfide (As2S3) via liquid-phase exfoliation of the naturally occurring mineral, orpiment. The resultant nanosheets had mean lateral dimensions and thicknesses of 400 and 10 nm, and had structures indistinguishable from the bulk. The nanosheets were solution mixed with carbon nanotubes and cast into nanocomposite films for use as anodes in potassium-ion batteries. These anodes exhibited outstanding electrochemical performance, demonstrating an impressive discharge capacity of 619 mAh/g at a current density of 50 mA/g. Even after 1000 cycles at 500 mA/g, the anodes retained an impressive 94% of their capacity. Quantitative analysis of the rate performance yielded a capacity at a very low rate of 838 mAh/g, about two-thirds of the theoretical capacity of As2S3 (1305 mAh/g). However, this analysis also implied As2S3 to have a very small solid-state diffusion coefficient (∼10-17 m2/s), somewhat limiting its potential for high-rate applications.
Keywords: 2D nanosheets; arsenic disulfide (As2S; orpiment; two-dimensional materials, arsenic disulfide, liquid-phase exfoliation, nanosheets, K-ion battery anodes, rate performance; 2D nanosheets; arsenic disulfide (As2S; orpiment